The Oxford handbook of early evangelicalism - Yeager, Jonathan (Oxford University Press, 2022)
Contexts -- Churches and movements -- The culture of evangelicalism -- Personalities.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Evangelikale Theologie; Evangelikale Bewegung